2013
DOI: 10.1055/s-0033-1335582
|View full text |Cite
|
Sign up to set email alerts
|

First Experience Using Navigation-Guided Radiofrequency Kyphoplasty for Sacroplasty in Sacral Insufficiency Fractures

Abstract: Purpose: To evaluate the efficacy and safety of navigation-guided radiofrequency kyphoplasty for sacroplasty in patients with sacral insufficiency fractures. Methods: In this single-center retrospective observational study, four consecutive patients with sacral insufficiency fractures were treated with navigation-guided radiofrequency kyphoplasty for sacroplasty between April 2010 and May 2012. Symptom characteristics, pain duration and pain intensity were recorded for each patient. Cement extravasation was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…As reported by Klingler et al [16] and Eichler et al [17], we also observed a significant pain reduction in all patients. Klingler et al [16] found asymptomatic PMMA leakages in 100 % of their cases and Eichler et al in 5.5 %, in contrast to 0 % in our study. The approaches selected were possibly disadvantageous, taking into account the complex anatomy of the sacrum, as the approach chosen in the two studies was via the long axis [22], whereas we chose an approach via the short or transiliac axis [23,24].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As reported by Klingler et al [16] and Eichler et al [17], we also observed a significant pain reduction in all patients. Klingler et al [16] found asymptomatic PMMA leakages in 100 % of their cases and Eichler et al in 5.5 %, in contrast to 0 % in our study. The approaches selected were possibly disadvantageous, taking into account the complex anatomy of the sacrum, as the approach chosen in the two studies was via the long axis [22], whereas we chose an approach via the short or transiliac axis [23,24].…”
Section: Discussionsupporting
confidence: 90%
“…As early as the second postoperative day, a significant pain reduction to an average of 2.3 score points can be seen. This remained consistently stable over the further course, at 2.2 after 6 months and 2.1 after 12 months [15][16][17], we also treated 20 patients with osteoporotic insufficiency fractures of the sacrum by means of radiofrequency-guided cement insertion. As reported by Klingler et al [16] and Eichler et al [17], we also observed a significant pain reduction in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the positive effect of sacroplasty can be counteracted by complications, with not always asymptomatic cement leakages at the forefront [8,12,27,28], although most do remain free of symptoms [22,29]. Cement leakage can be further reduced in BSP by the use of a balloon catheter, with which a cavity is created in the fracture zone and potentially leaking fracture gaps are compressed [13,16,21,25].…”
Section: Discussionmentioning
confidence: 99%